Parallel algorithms and architectures - Cosnard, M. (Michel) (International Thomson Computer Press, 1995)
Developments in parallel computing in recent years have made it possible to build multi-processor architectures that enable efficiency and speed in today's computing environment. Parallel Algorithms and Architectures provides a thorough introduction to this technology, explaining the fundamentals of parallelism in a logical and readable way. Progressing from theory to implementation, the text develops the algorithms of vector processors, shared-memory parallel machines and distributed-memory machines emphasising the link between architectures, models and algorithms. In addition, the book addresses a number of issues that are of great practical importance to people developing parallel programs, including coverage of LINPACK and BLAS, vectorisation, task placement and scheduling. Parallel Algorithms and Architectures is ideal for both computer science students and people in industry who require an understanding of parallelism.